Leukoreduction makes a difference: A pair proteomics study of extracellular vesicles in red blood cell units. (June 2021) - Tzounakas, Vassilis L.; Stamoulis, Konstantinos E.; Anastasiadi, Alkmini T.; Papassideri, Issidora S.; Kriebardis, Anastasios G.; Rinalducci, Sara; Antonelou, Marianna H.
Abstract: Prestorage filtration of blood to remove contaminating donor leukocytes and platelets has substantially increased the safety level of transfusion therapy. We have previously shown that leukoreduction has a mitigating effect on the storage lesion profile by lowering the extent of hemolysis and of RBC aging and removal phenotypes, including surface signaling and microvesiculation. Even though protein composition may determine the fate of EVs in the recipient, the probable effect of leukoreduction on the EV proteome has been scarcely investigated. In the present paired study, we characterized the proteome of EVs released in prestorage leukoreduced (L) and nonleukoreduced (N) RBC units prepared from the same donors, by immunoblotting and qualitative proteomics analyses at two storage intervals. Apart from common proteofrms typically associated with the established EV biogenesis mechanisms, the comparative proteomics analyses revealed that both leukoreduction and storage duration affect the complexity of the EV proteome. Membrane and cytoskeleton-related proteins and regulators, metabolic enzymes and plasma proteins exhibited storage duration dependent variation in L- and N-EVs. Specific proteoforms prevailed in each EV group, such as transferrin in L-units or platelet glycoproteins, leukocyte surface molecules, MHC HLA, histones and tetraspanin CD9 in N-units. Of note, several unique proteins have been associated with immunomodulatory, vasoregulatory, coagulatory and anti-bacterial activities or cell adhesion events. The substantial differences between EV composition under the two RBC preparation methods shed light in the underlying EV biogenesis mechanisms and stimuli and may lead to different EV interactions and effects to target cells post transfusion.